Kidney exchange match rates in a large multicenter clearinghouse. Issue 6 (9th March 2018) - Holscher, Courtenay M.; Jackson, Kyle; Chow, Eric K. H.; Thomas, Alvin G.; Haugen, Christine E.; DiBrito, Sandra R.; Purcell, Carlin; Ronin, Matthew; Waterman, Amy D.; Garonzik Wang, Jacqueline; Massie, Allan B.; Gentry, Sommer E.; et al.
Abstract : Kidney paired donation (KPD) can facilitate living donor transplantation for candidates with an incompatible donor, but requires waiting for a match while experiencing the morbidity of dialysis. The balance between waiting for KPD vs desensitization or deceased donor transplantation relies on the ability to estimate KPD wait times. We studied donor/candidate pairs in the National Kidney Registry (NKR), a large multicenter KPD clearinghouse, between October 2011 and September 2015 using a competing‐risk framework. Among 1894 candidates, 52% were male, median age was 50 years, 66% were white, 59% had blood type O, 42% had panel reactive antibody (PRA)>80, and 50% obtained KPD through NKR. Median times to KPD ranged from 2 months for candidates with ABO‐A and PRA 0, to over a year for candidates with ABO‐O or PRA 98+. Candidates with PRA 80‐97 and 98+ were 23% (95% confidence interval, 6%‐37%) and 83% (78%‐87%) less likely to be matched than PRA 0 candidates. ABO‐O candidates were 67% (61%‐73%) less likely to be matched than ABO‐A candidates. Candidates with ABO‐B or ABO‐O donors were 31% (10%‐56%) and 118% (82%‐162%) more likely to match than those with ABO‐A donors. Providers should counsel candidates about realistic, individualized expectations for KPD, especially in the context of their alternative treatment options. Abstract : In this study of a large, multicenter kidney exchange clearinghouse, median times to successful match range from two months to over a year, varying widely by candidate and donor ABO type and sensitization.